The Impact of Innovative Leadership in Achieving Sustainable Environmental Development A Field Study on Berber Cement Factory – Sudan (Sebha University Conference Proceedings, 2024)
The study aimed to investigate the impact of innovative leadership in achieving sustainable environmental development. The study employed a descriptive-analytical methodology and selected a sample of 63 employees from Berber Cement Factory. A questionnaire was used as a data collection tool. The study concluded that the level of innovative leadership and its dimensions was high, with a mean score of 3.94. There was a statistically significant impact of innovative leadership on sustainable environmental development in Berber Cement Factory, with an interpretation coefficient of 66.9%. The study recommended continuing to enhance a supportive work environment for innovation by providing more resources and support for employees to develop their innovative ideas and projects that contribute to environmental sustainability. It also emphasized the necessity of providing training and development programs for leaders in the company to enhance their innovative skills and guide them towards adopting sustainable environmental practices.